Team players and teamwork : - Parker, Glenn M. (Jossey - Bass Publishers, 1996)
This book will help you focus on what makes a good team player. It draws on stories of more than fifty team-driven organizations?including Xerox, Honeywell, General Motors, and 3M?to give you proven evidence of the qualities of high performing teams.